2017
DOI: 10.1037/rel0000055
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the unique role of religious coping in suicidal behavior among U.S. Iraq and Afghanistan veterans.

Abstract: In this study we examined relations of positive and negative religious coping with risk for suicidal behavior in a sample of Iraq and/or Afghanistan Veterans. Participants completed self-report instruments assessing risk for suicidal behavior, religious coping, general combat exposure, morally injurious experiences, depression, and posttraumatic stress disorder (PTSD) symptoms. Frequency analyses revealed that half of all participants endorsed being religious, and adaptively drawing on religion to cope was mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 25 publications
7
54
1
4
Order By: Relevance
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
“…Consistent pattern of associations was found in the case of negative religious coping and symptoms of disorders: depression (Ahrens et al, ; Henslee et al, ; Leaman & Gee, ), PTSD (Berzengi, Berzenji, Kadim, Mustafa, & Jobson, ; Cuevas et al, ; Currier et al, ; Gerber et al, ; Harris et al, ; Leaman & Gee, ; McCann & Webb, ; Park et al, ; Raines et al, ; Wortmann et al, ; Zukerman, Korn, & Fostick, —only in women; Zukerman, Korn, Shapiro, & Fostick, , avoidance symptoms), distress (Chan & Rhodes, ), suicidal ideations (Currier, Smith, & Kuhlman, ; Kopacz et al, ; Raines et al, ), and substance use (Raines et al, ). Lack of significant associations between the negative coping and symptoms of PTSD was demonstrated in Ahrens et al (), Al‐Hadethe et al (), and Chan and Rhodes ().…”
Section: Resultsmentioning
confidence: 68%
“…A considerable body of research has shown that exposure to PMIEs is associated with varied psychiatric symptoms among U.S. military personnel and veterans (Bryan, Bryan, Morrow, Etienne, & Ray‐Sannerud, ; Currier, Holland, Drescher et al., ; Currier, Holland, & Mallot, ; Currier, Smith et al., ; Dennis et al., ; Jordan, Eisen, Bolton, Nash, & Litz, ; Maguen et al., , ; Maguen, Vogt et al., ; Nash et al., ); Vietnamese veterans and civilians involved with the Vietnam War (Korinek, Loebach, & Teerawichitchainan, ); the Israeli Defense Force (Ritov & Barnetz, ); Portuguese Colonial War veterans (Ferrajão & Oliveira , , ); deployed healthcare providers (Gibbons, Shafer, Hickling, & Ramsey, ); professionals and parents involved with child protection services (Haight, Sugrue, & Calhoun, ; Haight, Sugrue, Calhoun, & Black, ); police officers (Komarovskaya et al., ); educators (Currier, Holland, Rojas‐Flores, Herrera, & Foy, ); and refugees (Nickerson et al., ). Furthermore, Wisco et al.…”
Section: Resultsmentioning
confidence: 99%
“…Relative to military personnel who have PTSD and deny exposure to PMIEs, those who present with symptoms attributed to both PTSD and moral injury were more likely to report suicidal thoughts and behaviors and to have attempted suicide (Bryan et al., ). Specifically, personnel who reported violating their own values (Maguen et al., ), rejected previously held religious beliefs (Currier, Smith et al., ), reported spiritual distress (Kopacz, Hoffmire, Morley, & Vance, ), or felt unforgivable (Bryan, Theriault, & Bryan, ) appeared more likely to attempt suicide in some cases. Evidence is mixed as to whether exposure to PMIEs is associated with aggressive behavior (Dennis et al., ; Maguen et al., ; Worthen & Ahern, ) or problematic substance use (Currier, Farnsworth et al., ; Maguen et al., ; Maguen, Luxton et al., ; Tripp, McDevitt‐Murphy, & Henschel, ).…”
Section: Resultsmentioning
confidence: 99%
“…These measures of religiosity were based on a single item, particularly perceived importance of religion, potentially relating to low reliability affecting study results. Religiosity is a multidimensional phenomenon, and its other aspects, such as religious affiliation or religious coping (Currier et al 2017), may more strongly moderate the complex relationship between stressful life events and thoughts of suicide (Lawrence et al 2016b). In addition, we were not able to disentangle the perceived importance of religion in relation to the perceived importance of spirituality.…”
Section: Discussionmentioning
confidence: 87%